Implantation of an Absorb bioresorbable vascular scaffold in the stenotic aortopulmonary collateral artery of a young child with Alagille syndrome. Issue 2 (22nd May 2015) - Castro Rodriguez, Jose; Dessy, Hugues; Demanet, Hélène
<x xml:space="preserve">Abstract</x> Stent implantation in children can be problematic due to the possibility of growth incapacity and difficulties during later surgery. For these reasons, bioresorbable stents may be a good alternative to conventional stents. We report our experience with implantation of an Absorb bioresorbable stent in the stenotic major aortopulmonary collateral artery (MAPCA) of a 1‐year‐old girl born with pulmonary atresia with ventricular septal defect. © 2015 Wiley Periodicals, Inc.